Cranial fracture that was diagnosed with direct graphy but not detected in cranial computerized tomography - Döşoğlu, Murat; İş, Merih; GEZEN, Ferruh; Aytekin, Hikmet (Cerrahpaşa Medical Journal, 2014)
Nowadays, there are some ideas that direct graphy is unnecessary for the evaluation of patients with head trauma. But, computerized tomography (CT) is less sensitive in detection of calvarial skull fractures than plain radiographs. We report a case who was admitted to hospital after fall and skull fracture was not detected with CT. Neurologic examination of the patient was normal when he was referred to our emergency department with complaints of headache, nausea, and vomiting. Plain radiograph showed right frontal lineer fracture so the patient was hospitalized. All cases who apply with head trauma are routinely evaluated with direct cranial graphy in our clinic because of legal conditions and the probability that transverse fractures may not be detected with CT.